Visualization and analysis of biomaterial-centered thrombus formation within a defined crevice under flow. (July 2016) - Jamiolkowski, Megan A.; Pedersen, Drake D.; Wu, Wei-Tao; Antaki, James F.; Wagner, William R.
Abstract: The blood flow pathway within a device, together with the biomaterial surfaces and status of the patient's blood, are well-recognized factors in the development of thrombotic deposition and subsequent embolization. Blood flow patterns are of particular concern for devices such as blood pumps (i.e. ventricular assist devices, VADs) where shearing forces can be high, volumes are relatively large, and the flow fields can be complex. However, few studies have examined the effect of geometric irregularities on thrombus formation on clinically relevant opaque materials under flow. The objective of this study was to quantify human platelet deposition onto Ti6Al4V alloys, as well as positive and negative control surfaces, in the region of defined crevices (∼50–150 μm in width) that might be encountered in many VADs or other cardiovascular devices. To achieve this, reconstituted fresh human blood with hemoglobin-depleted red blood cells (to achieve optical clarity while maintaining relevant rheology), long working optics, and a custom designed parallel plate flow chamber were employed. The results showed that the least amount of platelet deposition occurred in the largest crevice size examined, which was counterintuitive. The greatest levels of deposition occurred in the 90 μm and 53 μm crevices at the lower wall shear rate. The results suggest that while crevices may be unavoidable in device manufacturing, the crevice size might be tailored, depending on the flow conditions, to reduce the risk of thromboembolic events. Further, these data might be used to improve the accuracy of predictive models of thrombotic deposition in cardiovascular devices to help optimize the blood flow path and reduce device thrombogenicity.